Global Citizenship - Carrijo, Manuella [UNESP] (Open Book Publishers, 2022)
The word citizenship, a contested concept, emerges in different discourses that can hide contrasting interests. Differences in its meanings are enhanced with the changes in society through history. This chapter presents a discussion about mathematics education for citizenship and its outcomes. School presents itself as a stage of dispute and a space for expressing different ideologies that can configure ways of thinking and structuring an education on the topic of citizenship. Mathematics education is shown to be supportive of different citizenship discourses. In a globalised world with deep inequalities, a type of mathematics education for citizenship that matches with inclusion and diversity is required; one which considers global issues. The proposed landscape of investigation Global Visibility Matters is a possible support aid for mathematics classes, based on enabling students to develop global citizenship. By reading and interpreting a social situation as being open to change, it becomes possible for the students to be recognised as-and to act as-global citizens.